Smoking cessation improves health status of patients with chronic diseases: evidence from a longitudinal study of older adults in China - Haoyu Zhu; Peng Xu; Yumeng Wei; Chuchen Zhao; Danni Zhao; Yaxin Li; Xiaobin Ma; Meng Wang; Huafeng Kang (BMC Public Health)
Abstract Background Smoking is a well-documented risk factor for numerous chronic diseases, and cessation is correlated with enhanced health outcomes. Nonetheless, the precise effects of smoking cessation on the health status of older adults with chronic conditions in China have not been thoroughly quantified. Objective This study aims to quantitatively assess the correlations between smoking cessation and enhancements in the health outcomes of elderly Chinese individuals with chronic diseases. Method This research drew upon data from the China Health and Retirement Longitudinal Study (CHARLS). A cohort of 9914 participants was ultimately included in our analysis. Group comparisons and linear regression analyses were utilized. The investigation delved into health status scores, hematological markers, and physiological parameters. Result With each additional year of smoking cessation, former smokers demonstrated improved self-rated health and reduced EQ-5D-3L scores. Regression analysis unveiled a positive correlation between smoking cessation and enhanced self-assessed health (β estimate = 0.198), while a notable adverse effect was observed in EQ-5D-3L scores (β estimate = -0.179) and grip strength (β estimate = -2.530). Blood biomarkers also displayed noteworthy relationships with smoking cessation, showcasing rehabilitation in LDL cholesterol, total cholesterol, glucose, cystatin C, creatinine, HbA1c, and uric acid levels. Conclusion This research provides evidence highlighting the favorable health ramifications associated with smoking cessation in elderly individuals with chronic illnesses. Noteworthy improvements in both subjective health assessments and blood-based markers were observed post-smoking cessation, with benefits becoming more prominent with prolonged abstinence. These results underscore the vital importance of smoking cessation in the holistic care of chronic conditions and broader health enhancement endeavors. Further validation of these findings through an extended follow-up period is anticipated to bolster these conclusions with increased confidence.